Peran Perilaku Keuangan dalam Memediasi Faktor-faktor Yang Mempengaruhi Minat Menabung (Studi Kasus Individu Berkeluarga di Kota Malang) - Radinda Alifia Widarafika Putri; Farahiyah Sartika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The main objective of this paper is to identification how lifestyle, social environment, and financial literacy effect saving interest with a specific focus on the mediating role of financial behaviour among families in Malang. Using a quantitative method focused on numerical analysis, primary data were collected through Google Forms distributed to individuals within families in Malang. To determine the required sample size, the researcher used non probability sampling based on the formula by Hair Jr et al., (2023), and found that the sample size of individuals with familes was 170. The criteria for respondents were individuals with families who had been married for 5-10 years, resided in Malang City, and hade dependent children. The results suggest that lifestyle and social environment do not significantly affect saving interest, whereas financial literacy plays a crucial positive role. Although financial behaviour is influenced by lifestyle and literacy, it fails to act as a mediator because it does not significantly drive saving interest. This research shows that financial behaviour is not a variable that connects lifestyle, social environment, and financial literacy to an individual’s interest in saving.